Vegetative propagation of Eucalyptus species through polyglobule - Mamatha, M; Jalander, V; Venkateshwar Rao, B (Recent Research in Science and Technology, 2015)
Macro-propagation of Eucalypyus species is possible on large scale through relatively cheaper technique with polyglobule than automatic and low cost chambers. Further it also gives an added advantage in controlling diseases and their spread as it is confined to the specific polyglobule. The spread of the humidity and temperature in the polyglobule are uniform unlike other large mist chambers.